1977
DOI: 10.1038/bjc.1977.199
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up studies on the immune status of patients with Hodgkin's disease after splenectomy and treatment, in relapse and remission

Abstract: Summary.-Sixty-two patients with Hodgkin's disease have been followed for one year from the start of treatment. Immunological assessments were repeated after intensive treatment, in patients relapsing and in those in remission at one year. In patients achieving remission, overall cellular immunity, after deteriorating with therapy, particularly cytotoxic chemotherapy, returned to pre-treatment levels in remission when there was little evidence of cellular immune disturbance. Serum IgG and IgM levels fell with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
1

Year Published

1982
1982
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 14 publications
1
5
1
Order By: Relevance
“…Splenectomy has been claimed to have "protective" effects on peripheral leucocyte counts during therapy and our earlier study (Hancock et al, 1977) confirmed this. At 5 years, however, the neutrophil count was unchanged only in the radiotherapy/splenectomy group compared with the decreased level in other patients.…”
Section: Cellular Immunitysupporting
confidence: 69%
See 2 more Smart Citations
“…Splenectomy has been claimed to have "protective" effects on peripheral leucocyte counts during therapy and our earlier study (Hancock et al, 1977) confirmed this. At 5 years, however, the neutrophil count was unchanged only in the radiotherapy/splenectomy group compared with the decreased level in other patients.…”
Section: Cellular Immunitysupporting
confidence: 69%
“…However, leucocyte-migrationOther inhibition and lymphocyte-transformation asssessments were significantly lower at 5 years than at presentation, when responses were already subnormal. Since all these patients were in clinical remission when retested, these findings invalidate our previous suggestion (Hancock et al, 1977) that deteriorating cellular immunity may be a useful indicator of relapse. Our patients also showed falls in all the immunoglobulin classes (G, A and M) monitored over the period of study.…”
Section: Cellular Immunitycontrasting
confidence: 56%
See 1 more Smart Citation
“…In addition, despite efforts to educate patients and physicians to suspect the diagnosis and initiate adequate treatment promptly if disease occurs the annual mortality rate remains high (1.0–3.8%) [7]. Splenectomized individuals, in particular, patients with Hodgkin's lymphoma (HL) who have received chemotherapy, often show decreased serum immunoglobulin (Ig) levels of the IgM class [8–11]. As previously assumed by Kobel et al, if a young HL patient survives for 50 years after initial treatment, he/she runs a risk of 13.5 and 6.5% to develop and die from OPSI, respectively [12].…”
Section: Introductionmentioning
confidence: 99%
“…These conditions were considered being related to the onset of systemic VZV infection. Additionally, in Case 1, the relatively small spleen found by CT (spleen dysfunction is associated with reduction of humoral immunity [13]), the substantial blood transfusions, and the quadruple amputation were considered the other possible risk factors.…”
Section: Discussionmentioning
confidence: 99%